PENGARUH PENGGUNAAN MEDIA DIORAMA KONTEKS BENCANA ALAM TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V SD NEGERI KESTALAN SURAKARTA TAHUN AJARAN 2024/2025 - Yemima Glory Nausea Christi; Anggit Grahito Wicaksono; Elinda Rizkasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research explores how the use of diorama media impacts the learning outcomes of fifth-grade students in the Natural and Social Sciences (IPAS) subject at SD Negeri Kestalan Surakarta, with a focus on the topic of Natural Disasters. The study applied a quantitative method using a nonequivalent control group posttest-only design. A total of 67 students were involved, divided into 37 students in the experimental group and 30 students in the control group. Data were gathered through observation, teacher interviews, documentation, and a test comprising 20 multiple-choice items. Prior to use, the test was analyzed for validity, reliability, difficulty level, and discrimination index, resulting in 22 valid questions being selected. The results showed noticeable progress in both groups after the learning sessions. The control group achieved an average pretest score of 55.50, while the experimental group scored 60.14. Following the intervention, the control group’s posttest mean increased to 65.83, whereas the experimental group reached a higher average of 75.27. An independent t-test analysis indicated a significance value of 0.000 (<0.05), confirming that diorama media positively influenced students’ learning outcomes. Overall, the findings suggest that dioramas not only help students better understand abstract concepts of Natural Disasters by presenting them more concretely but also enhance their motivation and active participation in the IPAS learning process.